Basic principles and molecular mechanisms of olfactory axon pathfinding - Yoshihara, Yoshihiro; Mori, Kensaku (Cell and tissue research, 1997)
The present review describes several lines of recent evidence providing new insights into the basic principles and mechanisms of axon projection from the olfactory epithelium to the olfactory bulb. Olfactory sensory neurons are classified into approximately 1000 subtypes according to the expression of specific odorant receptors. Olfactory sensory neurons expressing a given odorant receptor are distributed within one zone out of the four circumscribed zones of the olfactory epithelium and send their axons to the corresponding zone of the olfactory bulb: the principle of zone-to-zone projection. We discuss possible functions of a novel cell adhesion molecule, viz., OCAM, in the formation and maintenance of zone-to-zone projection of both olfactory and vomeronasal axons. Furthermore, olfactory sensory neurons expressing a given odorant receptor converge their axons onto only two topographically fixed glomeruli among the 1500-3000 glomeruli in the olfactory bulb: the principle of glomerular convergence. These axonal connection patterns give rise to the response specificity of the second-order neurons, viz., the mitral/tufted cells, to a particular range of odor molecules. In the process of glomerular convergence, combinatorial functions of axon-associated cell adhesion molecules and odorant receptor proteins may be required for the establishment of the precise targeting of olfactory axons to the appropriate glomeruli.